Dampak Penerapan Anggaran Berbasis Kinerja Terhadap Akuntabilitas Kinerja Instansi Pemerintah Kabupaten Nagekeo-Flores - Samadara, Selfesina; Sir, Jennie S.; Poeh, Imelda M. (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
This study aims to determine the Impact of performance-based budgeting on Government Agencies' performance accountability in the Nagekeo-Flores Regency. The implementation of this performance-based budget utilizes four variables: budget planning (X1), budget implementation (X2), budget accountability (X3), and performance evaluation (X4). The Y variable is Performance Accountability. The study uses primary data. The population in this study consists of the budget and accounting sub-sections of the Financial and Regional Asset Management Agency of Nagekeo-Flores Regency. The analysis method used in this study is multiple linear regression. Based on the hypothesis test result in this study, the influence of budget implementation, consisting of budget planning, budget implementation, and budget accountability reporting, has a positive and significant effect, and performance evaluation has a negative and significant impact on the performance accountability of Nagekeo Regency Government agencies. Keywords: Budget, Performance, Accountability